2018
DOI: 10.1002/leap.1204
|View full text |Cite
|
Sign up to set email alerts
|

Peer review in the development of academic articles: Experiences of Finnish authors in the educational sciences

Abstract: This research examined author experiences of the developmental feedback regarding peer review of journal articles. It focused on quite experienced authors in the educational sector of all eight universities in Finland. Data were gathered using an electronic questionnaire, which was completed by 121 respondents. The majority of authors perceived reviewer feedback as developmental and appreciated critical but constructive review. Over 60% of respondents found reviewers usually keen to improve the article and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We believe that this is key to assess the developmental value of peer review as it allows us to examine how manuscripts change throughout the process of peer review (Atjonen, 2019;Bedeian, 2004;Matsui, Chen, Wang, & Ferrara, 2021;Rigby et al, 2018;Teplitskiy, 2016). For instance, the tendency of reducing the curation function of peer review to the goal of identifying impactful manuscripts via post-publication indicators (e.g., altmetrics, citations and other indicators), does not help to assess the quality of internal journal processes (Pontille & Torny, 2015;Seeber, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this is key to assess the developmental value of peer review as it allows us to examine how manuscripts change throughout the process of peer review (Atjonen, 2019;Bedeian, 2004;Matsui, Chen, Wang, & Ferrara, 2021;Rigby et al, 2018;Teplitskiy, 2016). For instance, the tendency of reducing the curation function of peer review to the goal of identifying impactful manuscripts via post-publication indicators (e.g., altmetrics, citations and other indicators), does not help to assess the quality of internal journal processes (Pontille & Torny, 2015;Seeber, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is little understanding of how this developmental function actually works [13][14][15][16]. While research on specific journals has shown that exposure to different rounds of peer review could increase the quality of manuscripts-including later submissions to other journals if rejected [17], other studies have suggested that reviewers are keen to preferably concentrate on theoretical aspects rather than rigour, methodology and statistical content [11,18].…”
Section: Introductionmentioning
confidence: 99%
“…2 The role of peer review in quality assurance in higher education and its links with sustainable development Peer review requires a collegiate approach between editors, reviewers and authors that, in the advancement of disciplines and professions, necessitates due courtesy, empathy and diligence from all (Desselle et al 2019). The importance of publishing for tenure, promotion and entry-level positions is recognized by authors (Teele and Thelen 2017), and they regard the contribution of peer reviewers beneficial for developmental feedback (Atjonen 2019), constructive comments (Roll 2019), and improvements to manuscript quality, readability and accuracy (Rowley and Sbaffi 2018). Editors across disciplines agree that the peer review process should critically assess manuscripts for clarity of thought, objectivity and knowledge (Pollock 2019), quality and methodological rigor (Roll 2019), novelty and significance (Alexandratos et al 2017), and it should demonstrate clear links to the aims and scope of the journal (Pollock 2019;Alexandratos et al 2017;Roll 2019).…”
Section: Introduction: Scientific Publications On Sustainability In H...mentioning
confidence: 99%
“…Authors have been accused of assessing publication value by impact factors or prestige, rather than the rigor and quality of each peer reviewed submission (Schimanski and Alperin 2018). Reviewer expertise and experience are also open to criticism, being blamed for the exercise of power, gatekeeping, paradigm contradiction and insufficient expertise (Atjonen 2019), as well as for providing descriptive praise or criticism, instead of practical guidance for improvement of manuscripts (del Fierro et al 2018). Even though peer reviewers are impartial experts (Roll 2019), there is recognition by editors that the peer review process is not without bias (Pollock 2019).…”
Section: Introduction: Scientific Publications On Sustainability In H...mentioning
confidence: 99%